2014
DOI: 10.3389/fnmol.2014.00034
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-modulated ROS-GC1 transduction system in testes and its presence in the spermatogenic cells

Abstract: ROS-GC1 belongs to the Ca2+-modulated sub-family of membrane guanylate cyclases. It primarily exists and is linked with signaling of the sensory neurons – sight, smell, taste, and pinealocytes. Exceptionally, it is also present and is Ca2+-modulated in t he non-neuronal cells, the sperm cells in the testes, where S100B protein serves as its Ca2+ sensor. The present report demonstrates the identification of an additional Ca2+ sensor of ROS-GC1 in the testes, neurocalcin δ. Through mouse molecular genetic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have shown that calcium ions were a decisive factor that affected sperm cell functions, including forward movement, activation, capacitation and acrosome reaction (Jankowska, Sharma, & Duda, ; Marin‐Briggiler et al, ). Accordingly, Ca 2+ ‐permeable channels and Ca 2+ transporters are found in sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that calcium ions were a decisive factor that affected sperm cell functions, including forward movement, activation, capacitation and acrosome reaction (Jankowska, Sharma, & Duda, ; Marin‐Briggiler et al, ). Accordingly, Ca 2+ ‐permeable channels and Ca 2+ transporters are found in sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies demonstrate a ROS-GC1 transduction system modulated by GCAP1 and S100B in plasma membrane of bovine testes (Jankowska et al, 2007 , 2014 ). Immuno-stainings establish that these components co-localize in bovine and human sperm (Jankowska and Warchol, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immuno-stainings establish that these components co-localize in bovine and human sperm (Jankowska and Warchol, 2010 ). A convergence of molecular genetics, biochemistry and immunohistochemistry disclose NCδ in male gonads (Jankowska et al, 2014 ). Thus, three sensors: GCAP1, S100B and NCδ, capture and transmit Ca 2+ signals to ROS-GC1 in this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Originally discovered in retina where they play an integral role in phototransduction in the outer segments of photoreceptors (Margulis et al, 1993 ; Goraczniak et al, 1994 ; Duda et al, 1996 ), ROS-GCs are also present in the photoreceptor cell bodies (Rambotti et al, 1999 ), photoreceptor synaptic region (Duda et al, 2002 ; Venkataraman et al, 2003 ), Muller cells (Rambotti et al, 1999 ) and in ganglion cells (Krishnan et al, 2004 ). Outside the retina, they are expressed in pinealocytes (Venkataraman et al, 2000 ), in olfactory bulb neurons (Duda et al, 2001 ), in the anterior portion of gustatory epithelium (Duda and Sharma, 2004 ) and in sperm (Jankowska et al, 2014 ). Thus, ROS-GCs direct multimodal cellular signal transductions (Sharma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%